Effect of second child intent on delivery mode after Chinese two child policy implementation: a cross sectional and prospective observational study of nulliparous women in Chongqing. Issue 12 (26th December 2017) - Zhao, Jianlin; Shan, Nan; Yang, Xiaochang; Li, Qin; Xia, Yinyin; Zhang, Hua; Qi, Hongbo
Abstract : Objectives: To assess the influence of second child intent on the delivery preferences and final delivery modes of nulliparous women, particularly caesarean delivery on maternal request (CDMR), after implementation of China's two child policy. Design: Cross sectional and prospective observational study. Setting: A tertiary teaching hospital in Chongqing, China. Participants: 1000 low risk nulliparous women were initially involved, and were divided into two groups based on their intent on having a second child. 814 women who completed all interviews were analysed. Main outcome measures: Preferred mode of delivery in second trimester and at admission; final delivery mode, CDMR. Results: 814 women who completed all interviews were analysed, in whom 51.2% intended to have a second child. The preference for caesarean delivery (CD) at the second trimester between the intent and no intent group was 6.2% versus 17.9% (adjusted RR 0.35, 95% CI 0.20 to 0.63) and increased to 24.2% versus 37.3% (adjusted RR 0.65, 95% CI 0.45 to 0.94) at admission, respectively. The overall CD rates between the two groups were 41.0% versus 50.4% (adjusted RR 0.84, 95% CI 0.60 to 1.18), and the CDMR rates were 16.7% versus 29.0% (adjusted RR 0.56, 95% CI 0.37 to 0.86), respectively. Conclusions: Women who intend to have a second child are less likely to request a CD, and high rates of CD and CDMR in nulliparous women may have decreased after implementation of China's two child policy.